Living Hadith ‘Buka Luwur’ Sunan Kudus - Arif Friyadi (Santri: Journal of Pesantren and Fiqh Sosial, 2021)
Living hadith is the response of certain Muslim communities in applying the words that come directly from the Prophet. This response occurs both in the form of personal and community in interpreting certain hadiths. Living hadith is seen as an acculturation between Islamic teachings and community phenomena in local culture. One of the living traditions that has developed in the Kudus community since the 16th century is the celebration of the buka luwur of Sayyid Ja'far Sadiq, Sunan Kudus. This tradition is commemorated by the people of Kudus as the haul of Sunan Kudus which falls on the 10th of Sura (Muharram). The research was conducted using library research methods and field research in Kauman Village, Kudus City which became the center of the spread of Islam in the 16th century. This social phenomenon is categorized as living hadith because there are several indications, including; 1) This tradition is inspired by the turn of the kiswah of the Kaaba; 2) This tradition is considered by the Kudus community as a tribute to the services of Islamic preachers in the Kudus, namely Sayyid Ja'far Sadiq, Sunan Kudus; 3) This tradition is considered to be based on hadith. From this phenomenon emerged a strong Islamic motivation in the form of generosity and inner satisfaction with respect to the first Islamic spreader on the island of Java.